PERANAN KUALITAS KEHIDUPAN KERJA DALAM MEMBANGUN KOMITMEN KEORGANISASIAN: STUDI EMPIRIK PADA BANK MILIK NEGARA DI JAKARTA - Hanes Riady (Faculty of Economics and Business, Universitas Gadjah Mada, 2007)
EOC (Employee Organizational Commitment) regarded as work attitude lately hasalways been a strategic issue and is believed to be something essential that must be won by anyorganization for it influences behaviors that lead an organization to functioning effectively.Hipothetically, the EOC is determined by QWL (Quality of Work Life). This research was aimedat finding out the most dominant determinants of EOC in state-owned banks in Jakarta. Thesewould then serve as solution variables to formulating strategy in winning the EOC. This appliedexplanatory research used the hypothetico-deductive method and path analysis. Two hundredand forty-nine respondents participated in this study. All of the hypotheses were empericallysupported and this meant the QWL subvariables have jointly influenced the EOC. Theinfluencing QWL subvariables serving as solution variables were financial compensation,advancement opportunities and job characteristics. The strategies and operations based on thesesolution variables had been formulated to winning the EOC.Keywords : EOC, QWL, financial compensation, job characteristics, advancement opportunities